Repertorio de Tacticas del Movimiento Feminista en la Region de la Araucania, Chile. Periodo 1990 a 2020 - Mora-Guerrero, G (UNIV CATOLICA TEMUCO, 2025)
We analyzed the tactics of the feminist movement in the Region of Araucania, Chile, between 1990 to 2020 from testimonies of women who self-ascribe to this mobilization. Based on the transformations that feminism has had in Latin American countries from the eighties onwards, we proposed qualitative research with grounded theory design and empirical data accumulated from 2013 onwards. Our results showed that this movement has changed from the action of a few organizations to acquire a network character, maintaining other tactics as social activism, construction of identities, and improving gender awareness. We concluded by showing the wide repertoire of local feminist action and encouraging the investigation of its new challenges with logics which combine the local with the global.